BASIC PRINCIPLES OF THE WARSAW SYSTEM OF INTERNATIONAL CIVIL AVIATION AND ITS INFLUENCE ON THE DEVELOPMENT OF THE NATIONAL AVIATION UNIVERSITY - Vodolaskova, Kateryna; Makeieva, Olena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the study is a scientific and historical analysis of the Warsaw Convention of 1929 as a legal framework which is an effective tool used by international civil aviation. Research methods: the methodological background of the work is a comprehensive analysis of the conceptual foundations of rules relating to international transportation by air, stipulated by the Warsaw Convention of 1929. It is based on the method of historicism, analytics and comparisons, explanation, classification, as well as systemic. Results: the unification of private air law for international air transport became a priority very early in the history of aviation, as the first airlines capable of carrying passengers, mail and cargo were established very soon after the First World War. The complex external elements of such a question required the unification of law at a broad international level to prevent unforeseen conflicts of law and conflicts of jurisdiction. Thus, the Warsaw Convention signed on October 12, 1929, officially called the Convention on the Unification of Certain Rules Relating to International Air Transportation, has become one of the most important instruments of private international law. The Warsaw Convention is an international convention that regulates liability in the event of an accident for the international carriage of persons, baggage or cargo by aircraft for remuneration. It was the first comprehensive legal framework governing aviation internationally, playing an important role in supporting the development of the sector and establishing a set of principles, most of which are still valid and form the basis of modern aviation law. In such conditions the National Aviation University was founded and, on these principles, began to form as a powerful scientific, educational, methodical institution. Discussion: in addition to the historical value, as well as the possibilities of application in the educational process of this article, it is relevant for the formation of the philosophical principles of the development of the NAU. At the dawn of the founding of NAU, world civil aviation was also at the stage of formation and formation. The purpose of the 1929 Warsaw Convention was to protect the fledgling aviation industry from the devastating effects of unlimited liability for aircraft accidents. After more than 100 years, the air transportation industry has become stable and safe. In the same way, since its foundation, NAU has turned into a powerful scientific, methodical, educational institution in the aviation industry of Ukraine and the world.